Transformation of Human Resource Management in Green Economic Sustainability and Global Challenges - Dr. Abdul Wahab Samad (Journal of Center for Energy Policy and Human Resources Capacity Development, 2025)
This study aims to analyze the influence of external factors on the management and development of human resources (HR) within organizations. The findings indicate that technology, green economy, and global social policies significantly affect HR strategies, while business innovation has not yet shown a direct significant impact. Social entrepreneurship is also proven to play a role in shaping socio-environmental policies that influence HR management at the organizational level. Based on these results, it is recommended to integrate innovation and HR strategies, enhance HR capacity to address global disruptions, and mainstream sustainability values in HR practices. Further studies are advised to adopt qualitative approaches, mediation or moderation models, and longitudinal designs to deepen the understanding of the dynamic relationships among variables. The findings contribute both theoretical and practical insights for developing an adaptive, sustainable, and globally responsive HR management system